Proteome Analysis of Poplar Seed Vigor - Zhang, Hong; Wang, Wei-Qing; Liu, Shu-Jun; Møller, Ian Max; Song, Song-Quan (PloS one, 2015)
Seed vigor is a complex property that determines the seed's potential for rapid uniform emergence and subsequent growth. However, the mechanism for change in seed vigor is poorly understood. The seeds of poplar (Populus × Canadensis Moench), which are short-lived, were stored at 30 °C and 75 ± 5% relative humidity for different periods of time (0-90 days) to obtain different vigor seeds (from 95 to 0% germination). With decreasing seed vigor, the temperature range of seed germination became narrower; the respiration rate of the seeds decreased markedly, while the relative electrolyte leakage increased markedly, both levelling off after 45 days. A total of 81 protein spots showed a significant change in abundance (≥ 1.5-fold, P < 0.05) when comparing the proteomes among seeds with different vigor. Of the identified 65 proteins, most belonged to the groups involved in metabolism (23%), protein synthesis and destination (22%), energy (18%), cell defense and rescue (17%), and storage protein (15%). These proteins accounted for 95% of all the identified proteins. During seed aging, 53 and 6 identified proteins consistently increased and decreased in abundance, respectively, and they were associated with metabolism (22%), protein synthesis and destination (22%), energy (19%), cell defense and rescue (19%), storage proteins (15%), and cell growth and structure (3%). These data show that the decrease in seed vigor (aging) is an energy-dependent process, which requires protein synthesis and degradation as well as cellular defense and rescue.